Tingkat Stres Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa selama Pembelajaran Daring pada masa Pandemi COVID-19 - Dewa Ayu Agung Alit Suka Astini; I Wayan Eka Arsana; Nindya Ayu Wulandari (Aesculapius Medical Journal, 2022)
Due to the COVID-19 pandemic, the government issued a social policy. Social restriction policy has forced the medical faculties around the world to change their conventional learning system into an online learning system. An online learning system may cause some problems due to limited network and a change in the assessment system. This can have an impact on the mental health of students. The purpose of this study was to determine the stress level of students from the Faculty of Medicine and Health Sciences at Warmadewa University during online learning in the midst of COVID-19 pandemic. The research was carried out in December 2021, where the learning system at the Faculty of Medicine and Health Sciences, Warmadewa University was still largely carried out online learning. A descriptive method with a cross sectional design was used, with a total of 110 subjects. Data were collected using the Medical Student Stressor Questionnaire. The data were analyzed by descriptive statistical analysis and presented as a frequency distribution table.The results showed that most of the students experienced moderate stress (46.4%). Based on age, the highest stress level was found in students aged 21 years old (57,6%). Based on gender, most of the stress levels obtained were higher in female students (52,5%). Based on the class, the highest stress level was found in 2018 class students (57,1%). This research shows that most of the students of the Faculty of Medicine and Health Sciences at Warmadewa University experienced moderate stress in the brave learning system during the COVID-19 pandemic, especially at the age of 21, female, and class 2018.